Emerging Leadership Practices for Hybrid Work: The Role of Algorithmic Management Tools - Zeena Alsamarra'I; Niki Panteli; Blooma John (Australasian Journal of Information Systems, 2025)
This paper examines the impact of algorithmic management (AM) tools in the increasingly popular hybrid workplace and the emergence of novel leadership practices in hybrid work settings. Particularly, we explore the use of an Employee Experience Management (EXM) platform – Microsoft Viva – that has AM features in enabling emerging leadership practices influenced by algorithms. Using a qualitative approach with a case study design of a multinational organisation that adopted an EXM platform, the study findings reveal that AM tools contribute to emerging leadership practices that reflect inclusive, humanised, and multimodal modes of leadership – all of which are underpinned by analytics-enabled leadership. The combination of these modes of leadership and associated practices is believed to respond to the challenges in employees’ work environment and enhance the employee experience in a hybrid workplace.